Effect of gamma irradiation on cellulose nanofibers - Isamu Ogura; Akihiro Moriyama; Yoko Iizumi; Shigehisa Endoh; Katsuhide Fujita; Masanori Horie; Toshiya Okazaki; Tomohiko Matsuzawa (Journal of Wood Science)
Abstract Cellulose nanofibers (CNFs) are plant-derived nanomaterials with promising potential for sustainable applications. However, their aqueous dispersions are susceptible to microbial contamination, necessitating sterilization for long-term storage and applications in food, cosmetics, and toxicity testing. Although gamma irradiation effectively inactivates microorganisms, it can alter the physical and chemical properties of cellulose, especially at high doses. In this study, we evaluated the effects of low-dose gamma irradiation (1–25 kilo Grays, kGy) on four types of commercially available CNFs. The 2,2,6,6-tetramethylpiperidine-1-oxyl radical-oxidized CNFs (TO-CNFs) subjected to gamma irradiation showed decreased molecular weight, fiber length, hydrodynamic particle size, and glycosidic bond-related infrared (IR) peak intensity, along with increased reducing ends and C=O stretching-related IR peak areas, indicating glycosidic bond cleavage and fiber shortening. Similar changes were observed in phosphorylated CNFs (P-CNFs) and aqueous counter collision CNFs (ACC–CNFs). In contrast, mechanically fibrillated CNFs (MF-CNFs) exhibited minimal changes. The viscosity and dynamic modulus of TO-CNFs and P-CNFs decreased, likely due to degradation, whereas these properties increased in ACC–CNFs and MF-CNFs, possibly due to cross-linking effects. Given the broad distributions of molecular weight and fiber length in native CNFs, the effect of gamma irradiation at a few kGy appeared to be minimal. Our findings offer a valuable reference for determining optimal gamma radiation doses for sterilization while preserving the CNF properties.